1996
DOI: 10.1891/0047-2220.27.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors and Hospital Readmission Status of Older Persons with Cardiovascular Disease

Abstract: One hundred twenty-one (121) patients 55 years and older, having cardiovascular disease, were followed for 90 days to identify factors that might be used as predictors for hospital readmission. An initial step was to determine which health status or psychosocial measures would best discriminate between two readmission groups (readmission vs. no readmission). Four factors were univariately significant: physical health, personal adjustment, happiness, and number of secondary disorders. At the end of the specifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…However, in the Middleton et al [37] study of 121 patients hospitalized for cardiovascular disease, there was no relationship between baseline optimism/hope and 90-day all-cause readmissions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the Middleton et al [37] study of 121 patients hospitalized for cardiovascular disease, there was no relationship between baseline optimism/hope and 90-day all-cause readmissions.…”
Section: Resultsmentioning
confidence: 99%
“…In one study (Hoogwegt [35]), the SD of the psychological construct (Global Mood Scale; GMS [36]) was not provided, but population norm data for the measure was available in the same (cardiac) population [36], and this value was used instead. For an additional study (Middleton [37]), between-group differences in happiness scores were compared by readmission status using t tests; these were converted to an OR for readmissions associated with baseline happiness scores.…”
Section: Methodsmentioning
confidence: 99%
“…Trait PES has been associated with lower rates of stroke among non institutionalized elderly (Ostir et al, 2001), lower rates of re-hospitalization after coronary disease (Middleton and Byrd, 1996) and less pain among rheumatoid arthritic patients (Potter et al, 2000, as cited in Cohen et al, 2006.…”
Section: Positive Emotional Style (Pes)mentioning
confidence: 99%
“…4,5 Positive affect refers to mood states such as joy, activity, and cheerfulness, 6 and is not merely the opposite of negative affect, 7 as both types of affect can be present simultaneously. 8 High levels of positive affect have been associated with a decrease in hospital readmissions in patients with CAD, 9 lower incident hypertension, 10 a dampened physiological stress response, 11 and lower incident CAD, 12 whereas studies on the association between positive affect and survival showed mixed results. 5,13 Anhedonia (i.e., reduced positive affect) has been shown to independently predict all-cause mortality and major adverse clinical events (i.e., myocardial infarction, hospitalization, or coronary revascularization) 1 year after an acute cardiac event.…”
Section: Introductionmentioning
confidence: 99%